Optimization of physical education and training system based on machine learning and Internet of Things - Wang, Chenhang; Du, Cong (Neural computing & applications, 2022)
In order to improve the effect of physical education and training, this paper combines machine learning technology to identify sports training features and action prediction, and combines Internet of Things technology to process physical education and training data, and build a physical education and training system based on machine learning and Internet of Things. In order to solve some shortcomings of the original extreme learning machine, this paper gradually optimizes the hidden layer mapping and parameter optimization to further improve the accuracy of prediction. Moreover, this paper uses the Internet of Things technology to achieve long-term uninterrupted data collection, and after the data have been processed to a certain extent, an extreme learning machine is used to predict the situation of sports training. Finally, this paper designs experiments to verify the performance of the system. The research results show that the physical education and training system constructed in this paper have certain practical effects and can optimize the physical education and training process.